Stress-induced metabolic exchanges between complementary bacterial types underly a dynamic mechanism of inter-species stress resistance - Kapil Amarnath; Avaneesh V. Narla; Sammy Pontrelli; Jiajia Dong; Jack Reddan; Brian R. Taylor; Tolga Caglar; Julia Schwartzman; Uwe Sauer; Otto X. Cordero; Terence Hwa (Nature Communications, 2023)
Abstract Metabolic cross-feeding plays vital roles in promoting ecological diversity. While some microbes depend on exchanges of essential nutrients for growth, the forces driving the extensive cross-feeding needed to support the coexistence of free-living microbes are poorly understood. Here we characterize bacterial physiology under self-acidification and establish that extensive excretion of key metabolites following growth arrest provides a collaborative, inter-species mechanism of stress resistance. This collaboration occurs not only between species isolated from the same community, but also between unrelated species with complementary (glycolytic vs. gluconeogenic) modes of metabolism. Cultures of such communities progress through distinct phases of growth-dilution cycles, comprising of exponential growth, acidification-triggered growth arrest, collaborative deacidification, and growth recovery, with each phase involving different combinations of physiological states of individual species. Our findings challenge the steady-state view of ecosystems commonly portrayed in ecological models, offering an alternative dynamical view based on growth advantages of complementary species in different phases.